Implementasi Model Pembelajaran Berbasis Perencanaan Yang Efektif Untuk Meningkatkan Prestasi Siswa - Amandha Fhadillah Siregar; Fitri Syakira Ridwan; Safran Hasibuan (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
The learning model is a form of learning that is depicted from start to finish which is presented typically by the teacher. In other words, a learning model is a wrapper or frame for the application of a learning approach, method and technique. This writing uses the library research method, where the library research method is a method carried out using literature in the form of books, notes or reports of research results from previous research. The author has made observations at SD IT Al Hijrah and conducted an interview with one of the teachers in order to obtain valid information. Planning can also be defined as a way to anticipate and balance change. According to Uno, this definition assumes that change always occurs. Environmental changes must always be anticipated so that changes are balanced with changes in learning in schools or madrasas. Thus, planning has three meanings. First, planning is an effort to find a future form and an effort to achieve it. Second, planning means efforts to eliminate the gap between the present situation and the future. Third, planning is an effort to change conditions so that they are in line with changing environmental conditions.